A regurgitalite of the Middle Triassic (Muschelkalk) from Upper Silesia (Poland) - Niedźwiedzki, Robert; Surmik, Dawid; Chećko, Agnieszka; Salamon, Mariusz A (Geology, Geophysics and Environment, 2021)
A bromalite from the Middle Triassic (Muschelkalk) of southern Poland, Sadowa Góra Quarry, is herein described and interpreted as a regurgitalite. The fossils occurring within the regurgitalite are angular and have sharp edges. They are represented by common fragments of thin-shelled bivalves as well as rare crinoid and gastropod remains. The composition of the collected inclusion is different from that of the host rock. There are many candidates that could have produced the regurgitalite, including durophagous sharks, marine reptiles, the actinopterygian Colobodus, or nautiloids. Our finding adds to the emerging evidence of durophagous predation in the Triassic sea of Polish part of the Germanic Basin. It is the second record of a regurgitalite from the Muschelkalk of Upper Silesia.